The Improvement of The Web-Based Application “Sampahqu” to Enhance Data Management Efficiency at The Waste Bank - Agustina Christiani; Verel Salomo Ulyano Simatupang; Priskila Christine Rahayu; Laurence; Sylvia; Satriyanto Beka (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
SAMPAHQU as a waste collection company in Tangerang Selatan plays a crucial role in the circular economy. With the increasing number of customers and collaborating waste banks, the need for a waste deposit application that can be accessed by SampahQu, waste bank administrators, and customers has become evident. This application is intended to facilitate SampahQu in monitoring the volume and types of waste deposited, as well as the corresponding monetary transactions to be paid to customers or waste bank administrators. Additionally, customers and waste bank administrators can access information regarding the types and quantities of waste they have deposited, along with the earnings derived from these deposits. To address these requirements, a web-based waste deposit application has been developed, enabling access via mobile devices. Nonetheless, several issues have been identified during its implementation, such as the lack of a payment reporting feature to the waste bank and the absence of customer-specific reports grouped by waste bank. Consequently, this research focuses on the enhancement of the SampahQu application to improve its utility for waste banks and SampahQu customers.